Intel: a case study in capacity planning and strategy - Tomlin, Brian (Henry Stewart Talks, 2018)
This case study describes capacity planning at Intel. By dividing capacity planning into three distinct but interconnected planning phases and revisiting its long-range planning process quarterly, Intel has been able to plan successfully in the volatile world of computer processing. Because Intel believes capacity planning to be a key driver of its success it allocates significant resources to the practice.